Climate Change Shrinks and Fragments Salmon Habitats in a Snow‐Dependent Region. Issue 12 (28th June 2022) - Tonina, Daniele; McKean, James A.; Isaak, Daniel; Benjankar, Rohan M.; Tang, Chunling; Chen, Qiuwen
Abstract: Climate change threatens biodiversity through global alteration of habitats, but efficient conservation responses are often hindered by imprecise downscaling of impacts. Besides thermal effects, warming also drives important ancillary environmental changes, such as when river hydrology evolves in response to climate forcing. Earlier snowmelt runoff and summer flow declines are broadly manifested in snow‐dependent regions and relevant to socioeconomically important cold‐water fishes. Here, we mechanistically quantify how climate‐induced summer flow declines during historical and future periods cause complex local changes in Chinook salmon ( Oncorhynchus tshawytscha ) habitats for juveniles and spawning adults. Changes consisted of large reductions in useable habitat area and connectivity between the main channel and adjacent off‐channel habitats. These reductions decrease the capacity of freshwater habitats to support historical salmon abundances and could pose risks to population persistence in some areas. Plain Language Summary: The large majority of climate change research for aquatic organisms has focused on stream water temperature and discounted the importance of flow changes associated with evolving precipitation regimes. Using a high‐resolution stream topographic map that supported a series of linked flow and fish habitat quality models, our research describes how observed historical flow reductions and projected future reductions affect local habitat quality, distributions, and connectivity for a salmon population. We demonstrated that as climate change continues to change flow regimes in snow‐dependent regions, it will cause fragmentation and reduce the overall volume of available habitats in headwater streams where salmon and other cold‐water fish species spawn and grow during early life stages. Key Points: Warming from climate change accelerates runoff and decreases streamflow during low flow periods in many snow dependent regions Extended summer low flows reduce and fragment the capacity of freshwater habitats to support historical salmon abundances Climate adaptation actions for salmon should consider hydrologic changes and floodplain connectivity besides increasing water temperatures